Early neonatal mortality rate and the risk factors in Wangaya hospital - Made lndah Nastiti Utami Budha; Wayan Retayasa; Made Kardana (Indonesian Pediatric Society Publishing House, 2016)
Background The first week of life of a neonate is a critical period. In Asia, early neonatal mortality rate remains high. Objective To investigate early neonatal mortality rate and the risk factors in Wangaya Hospital. Methods A cross sectional study was carried out retrospectively on neonates registered at Perinatology Unit, Wangaya Hospital Denpasar, Bali since January 2006. The study was done from October to November 2007. Data was obtained from medical record, analyzed as univariate using chi-square test or Fisher's exact test and multivariate logistic regression analysis model. Results Early neonatal mortality rate in Wangaya Hospital was 38.7 per 1000 livebirths. Univariate analyses showed that there were five significant risk factors of early neonatal death, i.e., respiratory distress, asphyxia, birth weight less than 2500 grams, sepsis, and gestational age less than 3 7 weeks. Multivariate analysis showed that those five variables were significant as risk factors of early neonatal death i.e., OR (95% confidence interval) for respiratory distress: 16.8 (3.7 to 76.6)], asphyxia: 13.5 (6.1 to 29.9)], birth weight <2500 grams: 8.1 (3.3 to 19.9)], sepsis: 7.3 (3.1 to 17.1), and gestational age <37 weeks: 3.5 (1.6 to 7.8)]. Conclusions Early neonatal mortality rate in Wangaya Hospital remains high. Respiratory distress, asphyxia, birth weight <2500 gram, sepsis, and gestational age <37 weeks were independent risk factors of early neonatal death.